Elevating Social Sciences Learning Outcomes: TGT Type Cooperative Learning Model - Amir Pada; Faizal Amir (Universitas Pendidikan Ganesha, 2022)
Teachers are required to be able to master the right learning model in creating a conducive and enjoyable learning situation in order to enable students to be actively involved in discovering and exploring their knowledge. The TGT model is a type of cooperative learning model that collaborate three main activities, namely group learning, games, and matches between groups to achieve learning goals. The purpose of the research is to analyses student learning outcomes before and after the application of the TGT model and to find out the effect of using the TGT model on social studies learning outcomes. This research is quantitative research with the type of experiment. So the research design used is a quasi-experimental design with a non-equivalent control group design. Sampling in this study used purposive sampling, consisting of 20 students in each experimental and control class. The data needed, using data collection techniques, namely tests and documentation. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. The results showed that social studies learning outcomes increased after being given treatment in the form of using the TGT model and the learning mastery obtained was relatively high and there was an effect of applying the TGT cooperative learning model to student learning outcomes. So that with this research it is hoped that they can broaden their knowledge and skills so that they can update in developing this research so that it can be useful for improving the quality of education in Indonesia.